Chinese Learning Through Internet Inspired By Contructivist Learning Theory - Huang Yan (Bina Nusantara University, 2011)
With the changing concept of education, there is growing emphasis on “student-centered” principle. This is one of the characteristics of Constructivist learning theory. On network teaching Chinese, Constructivist learning theory is indispensable. This article is the design of online Chinese teaching which is basic on the Constructivist learning theory.